2012
DOI: 10.1007/s10237-012-0420-9
|View full text |Cite
|
Sign up to set email alerts
|

A fiber-based constitutive model predicts changes in amount and organization of matrix proteins with development and disease in the mouse aorta

Abstract: Decreased elastin in mice (Eln+/−) yields a functioning vascular system with elevated blood pressure and increased arterial stiffness that is morphologically distinct from wild-type mice (WT). Yet, function is retained enough that there is no appreciable effect on life span and some mechanical properties are maintained constant. It is not understood how the mouse modifies the normal developmental process to produce a functioning vascular system despite a deficiency in elastin. To quantify changes in mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 44 publications
5
34
1
Order By: Relevance
“…Similar results were obtained by [6], they applied a fiber-based constitutive model to mechanical data from aorta during postnatal development of WT and Eln+/-mice and obtained the model was capable of distinguishing elastin amounts and identifying trends during development. Regarding the temporal evolution of the material parameters, we observe significant deviations of the material parameters between the ApoE −/− and the control mice as well as for the different locations over the aorta (upper, lower, iliac) which clearly underlined our observations from the experiments.…”
Section: Discussionsupporting
confidence: 63%
“…Similar results were obtained by [6], they applied a fiber-based constitutive model to mechanical data from aorta during postnatal development of WT and Eln+/-mice and obtained the model was capable of distinguishing elastin amounts and identifying trends during development. Regarding the temporal evolution of the material parameters, we observe significant deviations of the material parameters between the ApoE −/− and the control mice as well as for the different locations over the aorta (upper, lower, iliac) which clearly underlined our observations from the experiments.…”
Section: Discussionsupporting
confidence: 63%
“…First, although elastin is often modelled as an isotropic material [25,[30][31][32], qualitative observations of elastin orientation suggested nearly circumferentially and nearly axially oriented fibres. Second, although we did not quantify their organization, there are nearly circumferentially oriented smooth muscle cells.…”
Section: 'Microstructurally Motivated' Passive Constitutive Modelmentioning
confidence: 99%
“…This finding suggests that changes in the distribution of collagen fibers could damage the function of the submucosal ganglia. Also, authors reported an increase in the number of collagen fibers in the aorta of aged mice [41] . In addition, authors showed that aging favored an increase in the diameter of collagen fibrils [42] , in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%